To Incarnate the Word: orality, reading and writing in the castilian prohetesses of the Renaissance - Graña Cid, María del Mar (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Between the Middle Ages and the modern times there was in Castile a phenomenon of female prophethood with great public impact. Among its main exponents are two tertiaries, the Dominican Maria de Santo Domingo and the Franciscan Juana de la Cruz. Both women incarnated the word of God in a particular way. We will analyze the systems of communication that those women used to be heard trying to assess the weight of the orality and writing in a time of change from an oral culture to a «civilization of writing» because here lie some important aspects of their prophetic announcement.